Desenvolvimento de método para a determinação simultânea de resíduos de agrotóxicos e medicamentos veterinários em solo por UHPLC-MS/MS - Vicari, Michele Camara de (2013)
Typically, soil is the final destination of pesticides applied in agriculture and of veterinary drugs employed in animal production. The global concern about the possible consequences of the increased use of these compounds is reflected in increasingly stringent regulations on the levels of residues in agricultural products, animal products and in the environment. This results in intensifying the demand for environmental certification, reduction of Maximum Residue Levels in food and the introduction of procedures for traceability in production processes. In this study, we compared different extraction methods: mechanical agitation, ultrasound and QuEChERS for the determination of 76 pesticides and 9 veterinary drugs in soil using Ultra High Performance Liquid Chromatography coupled to tandem Mass Spectrometry (UHPLC-MS/MS). The extraction method that showed the best results consisted of weighing 10 g of soil followed by the addition of 10 mL of water and kept at rest for 10 min. Then added 10 mL of acetonitrile containing 1% (v/v) acetic acid and proceeded with mechanical shaking for 15 min. Then, it was added 4 g of anhydrous magnesium sulfate and 1.7 g of anhydrous sodium acetate and shaked manually and vigorously for 1 min. Subsequently, the tube was centrifuged for 8 min (3400 rpm) and the extract was filtered and diluted (1:4, v/v) in water before analysis by UHPLC-MS/MS. The method was validated by evaluating several parameters, such as linearity of analytical curves, limits of detection and quantification (LOD and LOQ), matrix effect, as well as accuracy an precision in terms of percentage of recovery and RSD. The analytical curves prepared in solvent and in the blank matrix extract showed linearity for most compounds, with coefficients of determination greater than 0.99, and the standard curves prepared in "blank" matrix extract were used to evaluate the matrix effect. To verify the accuracy and precision of the method, fortification in four concentration levels (10, 25, 50 and 100 μg kg-1) we performed, and extracted in replicate (n = 6), resulting in recovery values between 70 to 120%, with RSD lower than 20% for most of the compounds. Values of method LOQ and LOD were from 3.0 to 7.5 μg kg-1 and from 10 to 25 μg kg-1, respectively. After validation, the method was applied to the determination of pesticides and veterinary drugs in real samples, it showed to be very efficient to be applied in routine analysis.